2021
DOI: 10.3390/ijms222111678
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Approach to Elucidate Cerebrospinal Fluid Changes in Dogs with Intervertebral Disc Herniation

Abstract: Herniation of the intervertebral disc (IVDH) is the most common cause of neurological and intervertebral disc degeneration-related diseases. Since the disc starts to degenerate before it can be observed by currently available diagnostic methods, there is an urgent need for novel diagnostic approaches. To identify molecular networks and pathways which may play important roles in intervertebral disc herniation, as well as to reveal the potential features which could be useful for monitoring disease progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…Although cellular senescence can cause IDD progression, the underlying mechanism is unclear [3,[7][8][9]. Proteomics studies are widely used to identify potential therapeutic targets for various diseases, including IDD [25,26]. In this study, we collected aging NP tissues from individuals with IDD for proteomics analysis and experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Although cellular senescence can cause IDD progression, the underlying mechanism is unclear [3,[7][8][9]. Proteomics studies are widely used to identify potential therapeutic targets for various diseases, including IDD [25,26]. In this study, we collected aging NP tissues from individuals with IDD for proteomics analysis and experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Follistatin-like-1(FSTL-1) is a kind of myokine and cardiokine modulating immune responses, cell proliferation, and differentiation through binding to TLR-4, Wnt receptors, and various growth factors. FSTL-1 has an adverse effect on disc homeostasis, accompanied by increased concentrations in the serum of IVDD patients, discs of rats with IVDD, and the cerebrospinal fluid of dogs with IVDD ( 125 , 141 ). Mechanistically, FSTL-1 promotes NP cell inflammation by activating the MAPK, Smads, or NF-κB signaling pathway ( 125 , 141 ).…”
Section: Myokines and Cardiokinesmentioning
confidence: 99%
“…FSTL-1 has an adverse effect on disc homeostasis, accompanied by increased concentrations in the serum of IVDD patients, discs of rats with IVDD, and the cerebrospinal fluid of dogs with IVDD ( 125 , 141 ). Mechanistically, FSTL-1 promotes NP cell inflammation by activating the MAPK, Smads, or NF-κB signaling pathway ( 125 , 141 ). Interestingly, the knockout of FSTL-1 during embryonic development leads to a decrease in vertebral cartilage and matrix anabolism, indicating its fundamental role in early IVD formation ( 142 ).…”
Section: Myokines and Cardiokinesmentioning
confidence: 99%
“…Importantly, it is believed to be a novel pan-neuronal calcium handling marker [ 7 ], associated with cancers [ 8 ], and stimulating insulin secretion [ 9 ]. According to the literature, NUCB1 protein is implicated in Alzheimer’s disease [ 10 , 11 ], other neurodegenerative diseases, or cellular processes known to be dysregulated early in tauopathy pathogenesis [ 12 ] such as synaptic plasticity, proteostasis, glucose metabolism, and mitochondrial function. Recently, a paper indicated that an adult-viable mutant that completely disrupts the G protein α-subunit binding and activates NUCB1 plays a neuroprotective role in the Drosophila model [ 13 ] of neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%